Dialogue - Ford, Jeffrey D.; Ford, Laurie W. (Academy of Management Review, 1995)
The article presents a response to an earlier article published in a 1995 issue of “Academy of Management Review” from Carini, Livingstone, and Palich. The author takes issue with the authors' assertion that logics are “heuristics.” The author of this criticism claims that logics tell us what is true or real; heuristics are much more flexible. Discussion of dialectics and trialectics and their relation to change follows. The authors argue that trialectics complements existing logics by adding a new dimension to the understanding and management of change.